"A Future to Believe in": Introducing Varieties of Advocacy Journalism. The Examples Sustainability and the Sanders Campaign. (3rd July 2020) - Laws, Norman; Chojnicka, Joanna
ABSTRACT: In this paper we argue that if social constructivism theory is to be taken seriously, the distinction between reportive journalism and advocacy journalism cannot hold anymore. We propose to use another working distinction between progressive (and also regressive) advocacy journalism, postulating forms of social change, and status quo advocacy journalism, which, directly or indirectly, postulates lack of change. To illustrate this distinction, we use two different examples that may seem unrelated. However, as we try to show, they are overlapping and intermingled. These examples are the different notions of sustainability and the coverage of the Sanders campaign during US primaries in 2016.